1998
DOI: 10.1073/pnas.95.24.14535
|View full text |Cite
|
Sign up to set email alerts
|

Promoting detachment of neutrophils adherent to murine postcapillary venules to control inflammation: Effect of lipocortin 1

Abstract: In this study we investigated, using intravital microscopy, how neutrophil extravasation across mouse mesenteric postcapillary venules is inhibited by the glucocorticoid-regulated protein lipocortin (LC; also termed annexin) 1. Intraperitoneal injection of 1 mg of zymosan into mice induced neutrophil rolling on the activated mesenteric endothelium followed by adhesion (maximal at 2 hr: 5-6 cells per 100-m of vessel length) and emigration (maximal at 4 hr: 8-10 cells per high-powered field). Treatment of mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 40 publications
8
163
1
2
Order By: Relevance
“…Furthermore, a previous study demonstrated that an overexpression of the human LXA 4 receptor in vivo could have a downstream effect on signal generation and reduce the number of PMN infiltrating into tissues (16). ANXA-1 has been shown to promote the detachment of neutrophils adhered to the inflamed endothelium, hence reducing the number of cells that migrate into the subendothelial space (51). In addition, the latter mediators have also been shown to prevent the production of TNF-␣ in various models of inflammation (52,53).…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 99%
“…Furthermore, a previous study demonstrated that an overexpression of the human LXA 4 receptor in vivo could have a downstream effect on signal generation and reduce the number of PMN infiltrating into tissues (16). ANXA-1 has been shown to promote the detachment of neutrophils adhered to the inflamed endothelium, hence reducing the number of cells that migrate into the subendothelial space (51). In addition, the latter mediators have also been shown to prevent the production of TNF-␣ in various models of inflammation (52,53).…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 99%
“…Briefly, 1 ϫ 10 6 U937 cells were radiolabeled by incubation in 100 l of RPMI containing 10% FCS and 20 Ci of 51 Cr (as sodium chromate) for 1 h at 37°C. After washing three times with HBSS labeled U937 cells were resuspended in RPMI 1640 medium containing 10% FCS, and were then incubated at 37°C for 30 min with or without human rANX1 (6). Next, 200 l (2 ϫ 10 5 ) labeled U937 cells, treated or not with ANX1, were added to each well of 96-well plates containing confluent HBMEC monolayers.…”
Section: Adhesion Of U937 Cells To Endothelial Cellsmentioning
confidence: 99%
“…Recombinant ANX1, annexin 5 (ANX5), and a chimeric protein ANX1-5, were expressed as GST-fusion proteins in pGEX vectors, as described (6). Fusion proteins were purified from bacterial lysates by affinity chromatography using prepacked glutathione-Sepharose 4B, and the GST moiety was removed by cleavage with thrombin (20).…”
Section: Abs Recombinant Proteins and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory activities elicited by exogenously applied annexin 1 are mediated through its unique N-terminal domain. Peptides derived from this domain, which are most likely generated at sites of inflammation and in coculture of neutrophils with activated endothelial cells, are not only true mimetics of the annexin 1 action in all inflammation models tested, but most likely are also the active entities with respect to the antiinflammatory actions described for annexin 1 (5,(7)(8)(9)(10)(11). Recently, it was shown that the inhibitory effect of the N-terminal annexin 1 peptides as well as full-length annexin 1 on the transendothelial migration of granulocytes is at least in part due to a peptidetriggered desensitization of the N-formyl peptide receptor (FPR) 3 on human granulocytes.…”
mentioning
confidence: 99%